Prevalence of Cardiovascular Disease Risk Factors in Vologda Oblast Districts - N. Kh. Svanadze; R. A. Kasimov; A. A. Orlovsky; N. V. Lazareva (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. There are large regional disparities in prevalence of non-communicable disease risk factors, as well as in the cardiovascular disease (CVD) incidence and mortality rates in Russian Federation (RF). Aim. To demonstrate the disparities in prevalence of CVD risk factors between Vologda Oblast districts. Materials and methods. Databases created in 2009 at the State-financed health institution of the Vologda Oblast «Vologda Regional Center for Medical Prevention», based on the results of a survey conducted within the framework of the World Health Organization CINDI program. CINDI questionnaire; cross-sectional study; the data was processed using R programming language and the Statistica software package 12. Results. The most common behavioral CVD risk factors in different Vologda Oblast districts included inadequate fruits and vegetables consumption (30–90%) and alcohol abuse (40–80%); hypertension (40–60%), overweight and obesity (30–55%) were the most frequent biological CVD risk factors; the most prevalent socio-economic risk factors included low education level (75–90%) and unemployment (20–40%). Participants residing in rural municipalities differed from urban okrugs (cities) dwellers in a higher prevalence of smoking (p < 0.01), alcohol abuse (p < 0.001), inadequate fruits and vegetables consumption (p < 0.0001), overweight and obesity (p < 0.05), unemployment (p < 0.0001), low education level (p < 0.0001), as well as a low overall assessment of their health (p < 0.05). Conclusions. We detected disparities in CVD risk factors prevalence between Vologda Oblast districts in 2009. Both behavioral and biological CVD risk factors were more common in participants from rural municipalities. The CVD risk factors distribution between the RF subjects’ districts requires further scientific research.